La metodología de resolución de problemas y el desarrollo cognitivo : un punto de vista postpiagetiano - Pomés Ruiz, J. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
In this work we studied the influence of the problem -solving methodology used on the efficiency with which students' intellectual potential can be exploited. The paper shows the varying degree of interest of students in real problems as determined by application of straightforward exercises and describes the origin of the difficulties found by students in working out problems. Finally, the different methodologies were applied to questions on stoichiometry topics and the results obtained on analysing errors made by students in their replies testified to the validity of the thesis originally put forward.